Time-mortality relationships for Cadra (Ephestia) cautella infesting walnut (Juglans regia) using thermal treatments - THAKUR, MANJU; BHALLA, SHASHI; RAWAT, SUDHIR; SINGH, SUBADAS; KHETARPAL, R K (The Indian Journal of Agricultural Sciences, 2011)
Laboratory experiments were conducted at National Bureau of Plant Genetic Resource, New Delhi during 2008–09 to determine the time-mortality response relationship of different developmental stages of Cadra (Ephestia) cautella (Wolker), viz egg, early larva, late larvae, pupa and adult infesting kernel and in-shell walnut kernel exposed to thermal treatment at 50°C for different durations. Mortality of each stage increased with the increase in exposure time. Egg was found to be the most tolerant stage, followed by late larva, early larva, pupa and adult. The 99% (LT99) mortality of early larva, late larva and pupa in kernel and in-shell walnut kernel was achieved within <41 min. of exposure period at 50°C, while for the egg (most tolerant stage) in in-shell walnut kernel LT99 was 121.97 min. and LT50 was 34.03 min. Adult was the most susceptible stage to heat and complete mortality was achieved within 20 min of exposure. No aberrations occurred in organoleptic test and also there was no significant difference in the moisture content after 45 days of storage of kernel in shell and walnut kernel kept in airtight containers at 10°C. These results provide a basis for successful use of thermal treatments for management of all the life stages of C. cautella in kernel and in-shell walnut kernel.